Perlindungan Hukum UMKM terhadap Praktik Predatory Pricing di Social Commerce: Studi Analisis pada Platform TikTok di Indonesia - Afif Syafiuddin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the legal protection afforded to UMKM against predatory pricing practices in social commerce, with a focus on the TikTok platform in Indonesia. Predatory pricing refers to a strategy of selling goods at extremely low prices with the intent to eliminate competitors, which poses a threat to the sustainability of UMKM in the digital market. As MSMEs increasingly adopt digitalization and utilize e-commerce platforms, the challenges related to unfair business competition practices have become more evident. This study employs a qualitative approach with a descriptive-analytical method, examining the relevant regulations, including Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The findings indicate that although regulations are in place, their implementation on digital platforms still faces various obstacles, such as weak supervision and difficulties in law enforcement. This study recommends enhancing oversight, providing education for UMKM, and simplifying legal procedures to strengthen the protection of MSMEs against predatory pricing in the digital era.